2013
DOI: 10.1016/j.cub.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Fructose Content Is Controlled by the Vacuolar Transporter SWEET17 in Arabidopsis

Abstract: In higher plants, soluble sugars are mainly present as sucrose, glucose, and fructose. Sugar allocation is based on both source-to-sink transport and intracellular transport between the different organelles and depends on actual plant requirements. Under abiotic stress conditions, such as nitrogen limitation, carbohydrates accumulate in plant cells. Despite an increasing number of genetic studies, the genetic architecture determining carbohydrate composition is poorly known. Using a quantitative genetics appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
225
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 227 publications
(259 citation statements)
references
References 21 publications
7
225
0
9
Order By: Relevance
“…S12B; data not shown). It is possible that the lower uptake activity mediated by SWEET16 (K m higher than 10 mM measured in an oocyte expression system; Klemens et al, 2013), compared with SWEET17 (K m lower than 10 mM measured in the same oocyte expression system; Chardon et al, 2013), on the tonoplast was below the detection limit due to a high background ( Fig. 6A; Supplemental Fig.…”
Section: Clade IV Sweets Function As Vacuolar Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…S12B; data not shown). It is possible that the lower uptake activity mediated by SWEET16 (K m higher than 10 mM measured in an oocyte expression system; Klemens et al, 2013), compared with SWEET17 (K m lower than 10 mM measured in the same oocyte expression system; Chardon et al, 2013), on the tonoplast was below the detection limit due to a high background ( Fig. 6A; Supplemental Fig.…”
Section: Clade IV Sweets Function As Vacuolar Transportersmentioning
confidence: 99%
“…The T-DNA insertion mutants for SWEET17 (sweet17-1 and sweet17-2; Chardon et al, 2013) and SWEET16 (sweet16-1 and sweet16-2) were obtained from the Salk Institute Genomic Analysis Laboratory (http://signal.salk.edu/ cgi-bin/tdnaexpress): SM_3_15143, as sweet16-1, and SM_3_30077, as sweet16-2.…”
Section: Identification Of Sweet16 and Sweet17 Insertion Mutantsmentioning
confidence: 99%
“…The mutant of AtSWEET17 plants are dwarfed and have a low seed yield, suggesting that AtS-WEET17 plays a role in the carbon distribution of plants (Chardon et al 2013). OsSWEET14 deletion mutation to the decrease of plant seed size and development delay.…”
Section: Expression and Putative Functions Of Sweetsmentioning
confidence: 99%
“…Other SWEETs have the function of transporting fructose and galactose (Klemens et al 2013;Guo et al 2014;Zhou et al 2014). AtSWEET16 and AtSWEET17 are highly expressed in roots and involved in the transport of monosaccharides and polysaccharides across tonoplast (Klemens et al 2013;Guo et al 2014;Chardon et al 2013). In addition, SWEETs participate in the transport of sugar and ions.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent quantitative trait locus analysis, we identified SWEET17 as a novel determinant of leaf Fru content, especially under cold conditions and conditions of low nitrogen supply (Chardon et al, 2013). In fact, a detailed molecular-physiological analysis revealed that SWEET17 is the first vacuole-located SWEET protein and that it serves as a Fru-specific exporter, connecting the vacuolar lumen to the cytosol.…”
mentioning
confidence: 99%